GC-MS Analysis of n-Hexane Extracts of Hibiscus micranthus Linn. - Ashok Kumar, K.; Ramachandra Setty, S.; Lakshmi Narsu, M. (Asian Journal of Chemistry, 2010)
Hibiscus micranthus Linn., is an undershurb which grows wild in India, Ceylon, tropical African-hexane extracts of Hibiscus micranthus Linn., with the help of GC-MS technique. The n- hexane extraction of the powder of dried leaves, stem and root parts of Hibiscus micranthus Linn., by Soxhlet extraction yielded thick green residue (leaves and stems) and red thick residue (roots), respectively, which were analyzed by the GC-MS. A total of 23 compounds were identified from the extract are tetramethyl, 1-octanol-2-butyl, cyclopentadecanol, octadecane, phosphonofluoridic acid (1-methylethyl)-cyclohexyl ester. However cylcopentadecanol was the most abundant followed by oleic acid. From the acid-14-methyl, methyl ester, 9,12-octadecadienoic acid methyl ester, cyclopropanepentanoic acid-2-undecyl-methyl ester and oleic acid were the major components of the stem extract and the oleic acid was the most abundant one. Thirty nine compounds were identified from the GCMS analysis of the dihydrocarveol, 1,2,4-trioxolane-2-octanoic acid 5-octyl-methyl ester, ester, 4-germaspiro(3,4)octane, cinerin-II, 4-decen-6-ynedioic acid dimethyl ester, 1- 1,25-dihydroxycholecalciferol, naptho(3,2,1-c,d)isoindol-4(5 , 1,3,2-dioxarsenane-4-methyl-2-phenyl-, methyl-2,3,4-tri-O-acetyl-6-O-methyl- 1,2-dicarbadodecaborane 1-hexyl- and 1,2,3,6,9-pentaazaspiro(4,4)non-2- ene,1,4,4,6,9-pentamethyl-, were the major components of the root extract and cinerin-II was the most abundant one followed by 4-germaspiro(3,4)octane. The GC-MS analysis revealed that the aldehydes and ketones (together 13.8 %), sulphur compounds (8.3 %), fatty acids, esters and alcohols were least (5.5 %), while stem extracts composed fatty acid esters (33.3 %) followed by fatty acids (14.8 %) and least in hydrocarbons (3.7 %). The non-polar root extract composed fatty acid esters (19.1 %) followed by aldehydes and ketones (13.2 %), hydrocarbons (10.2 %), fatty alcohols (8.8 %) and least were fatty acids. It is concluded that the leaf, stem and root of of phytopharmaceutical importance. n-hexane extract of leaf of H. micranthus Linn. The major components of the leafβ-ionone, cyclopentane carboxylic acid, decyl ester, oleic acid, hexadecane 2,6,10,14-n-hexane extract of the stem, 14 compounds were identified. Pentadecanoicn-hexane root extract of H. micranthus Linn. 2-(Methyl)-cycloheptanone,n-heptanoic acid methylα-18O-H)-one-2-hydroxy-1,5-dimethoxy-α-Dgalactopyranoside,n-hexane extract of leaves are mainly composed of hydrocarbons (25 %) followed byn-hexane extracts ofHibiscus micranthus Linn., contains various potent bioactive compounds and Saudi Arabia. The plant is used as a febrifuge in the traditional medicine in Saudi Arabia and in Ceylon. The current study is aimed at to characterize the non-polar chemical components from